Session Topic: The Flow of Funds and Interest Rates-I: U.S. Financial Models: Discussion - Goldfeld, Stephen M.; Meltzer, Allan H. (Journal of Finance, 1974)
Stephen M. Goldfeld, Allan H. Meltzer, Session Topic: The Flow of Funds and Interest Rates-I: U.S. Financial Models: Discussion, The Journal of Finance, Vol. 29, No. 2, Papers and Proceedings of the Thirty-Second Annual Meeting of the American Finance Association, New York, New York, December 28-30, 1973 (May, 1974), pp. 358-363